Histopathological Analysis of Cerebrovascular Lesions Associated With Aging. Issue 2 (7th December 2021) - Dallaire-Théroux, Caroline; Saikali, Stephan; Richer, Maxime; Potvin, Olivier; Duchesne, Simon
Abstract: Cerebrovascular disease (CVD) has been associated with cognitive impairment. Yet, our understanding of vascular contribution to cognitive decline has been limited by heterogeneity of definitions and assessment, as well as its occurrence in cognitively healthy aging. Therefore, we aimed to establish the natural progression of CVD associated with aging. We conducted a retrospective observational study of 63 cognitively healthy participants aged 19–84 years selected through the histological archives of the CHU de Québec. Assessment of CVD lesions was performed independently by 3 observers blinded to clinical data using the Vascular Cognitive Impairment Neuropathology Guidelines (VCING). We found moderate to almost perfect interobserver agreement for most regional CVD scores. Atherosclerosis (ρ = 0.758) and arteriolosclerosis (ρ = 0.708) showed the greatest significant association with age, followed by perivascular hemosiderin deposits (ρ = 0.432) and cerebral amyloid angiopathy (CAA; ρ = 0.392). Amyloid and tau pathologies were both associated with higher CVD load, but only CAA remained significantly associated with amyloid plaques after controlling for age. Altogether, these findings support the presence of multiple CVD lesions in the brains of cognitively healthy adults, the burden of which increases with age and can be quantified in a reproducible manner using standardized histological scales such as the VCING.